Agile approach to stunting data integration: an extreme programming perspective - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
Child stunting is a global health problem requiring a holistic approach, including integrating health data for effective monitoring and analysis. This research was motivated by the need to develop a stunting data integration application responsive to change and meeting user needs. The extreme approach of Extreme Programming (XP) was the main focus of this endeavor due to its potential to improve team collaboration and software quality. The research involved three main stages: data collection, application development, and user needs analysis. The results showed that applying the XP approach effectively improved team collaboration, responsiveness to change, and software quality. Testing of application features and user acceptance evaluations reflected the application's success in meeting user expectations and needs, with satisfaction levels reaching 87 percent, according to stakeholder testing results. This research makes an essential contribution to stunting data integration application development. The XP approach proved its effectiveness in this context and opened the door for further research and development in the application of agile methods in the health sector.